Multicentric Round Cell Neoplasms and Their Viral Associations in Wild Turkeys (Meleagris gallopavo) in the Southeastern United States. Issue 6 (November 2019) - Niedringhaus, Kevin D.; Nemeth, Nicole M.; Sellers, Holly S.; Brown, Justin D.; Fenton, Heather M. A.
Multiple oncogenic viruses, including lymphoproliferative disease virus (LPDV) and reticuloendotheliosis virus (REV), have been detected in wild turkeys ( Meleagris gallopavo ). The prevalence of infection with these viruses appears to be more common than overt disease; thus, data on the manifestation of associated disease in wild turkeys are scarce. Diagnostic records from wild turkeys submitted to the Southeastern Cooperative Wildlife Disease Study from 1980 to 2017 were reviewed to identify cases of neoplasia. Neoplasia was reported in 59 of 851 (6.9%) wild turkeys submitted. Of the cases of neoplasia tested by polymerase chain reaction, LPDV was detected in 34 of 58 (59%), REV in 10 of 39 (26%), both viruses in 3 of 39 (8%), and no retroviruses detected in 5 of 39 (13%) turkeys. The most common gross lesions observed among turkeys with neoplasms were emaciation (30/40; 75%); nodules in the skin (26/59; 44%), liver (17/59; 29%), or spleen (9/59; 15%); and splenomegaly (14/59; 24%). Microscopically, nodules were composed of pleomorphic round cells with large eccentric nuclei and prominent nucleoli resembling lymphocytes or lymphoblasts (57/59; 97%) except for 2 cases, one of myeloid cell origin and the other with primarily spindloid cells. This study indicates the need to characterize the pathogenesis and potential health threat posed by REV and LPDV to wild turkeys. Experimental infection studies and the development of additional diagnostic tests to confirm the role of retroviruses in lymphoproliferative disease are warranted.